Immunization of high-risk paediatric populations: Central European Vaccination Awareness Group recommendations. (June 2014) - Richter, Darko; Anca, Ioana; André, Francis E; Bakir, Mustafa; Chlibek, Roman; Čižman, Milan; Mangarov, Atanas; Mészner, Zsófia; Pokorn, Marko; Prymula, Roman; Salman, Nuran; Šimurka, Pavol; et al.
<x xml:space="preserve">Abstract</x> Over the last decade, childhood immunization has substantially reduced morbidity and mortality from vaccine-preventable diseases. However, particular paediatric risk groups, such as those with comorbidities, may not be adequately vaccinated despite being more susceptible to complications and death from certain infectious diseases. This may be due to lack of immunization recommendations, lack of awareness, or incomplete adherence to existing guidelines. Furthermore, recommendations for immunization can be inconsistent across Europe. An expanded initiative from the Central European Vaccination Awareness Group aims to raise awareness of the different high-risk paediatric groups, differentiate them according to their specific risk, and formalise a guidance statement for the immunization of each population.